Macroeconomic factors in modelling the SMEs bankruptcy risk. The case of the Polish market - Ptak-Chmielewska, Aneta; Matuszyk, Anna (Czynniki makroekonomiczne w modelowaniu ryzyka upadłości MŚP. Przykład rynku polskiego, 2019)
The last financial crisis affected the SMEs sector in different countries at different levels and strength. SMEs represent the backbone of the economy of every country. Therefore, they need bankruptcy prediction models easily adaptable to their characteristics. In our analysis we verified hypothesis: including information about macroeconomic conditions significantly increases the effectiveness of the bankruptcy model. The data set used in our research contained information about 1,138 SMEs. All information was taken from the financial statements covering the period 2002-2010. The sample included enterprises from sectors: industry, trade and services. Selected financial ratios were used to build the model and the macroeconomic variables were added: GDP, inflation, and the unemployment rate. Logistic regression as the research method was applied. In our study we showed that the incorporation of the macro variables improved the prediction of the SMEs bankruptcy risk
Econometrics = Ekonometria, 2019, Vol. 23, No. 3, s. 40-49
Keywords: bankruptcy risk model; logistic regression; macro variables; modele ryzyka upadłości; regresja logistyczna; zmienne makroekonomiczne